Motivating Content: How Interest and Self-Efficacy Respond to Subject Matter in an Alternative Teacher Education Program - Long, Joyce F.; Moore, Raeal (Catholic Education: A Journal of Inquiry and Practice, 2008)
Understanding how teachers’ motivational levels respond to the course content is particularly relevant in Catholic schools, where instructors are routinely required to teach courses both within and beyond their certification area because of budgetary constraints. Students in the ACE alternative licensure program face this challenge during their 2 years of teacher preparation. Pre and post data from first- and second-year ACE students (n = 107) revealed that although subject matter interest levels remained relatively robust throughout the academic year for primary certification subjects, significant differences emerged in scores for religion and other out-of-certification courses. In addition, sense of self-efficacy in classroom management, student engagement, and instructional strategies also varied by subject matter taught and year in the program.